NMR studies of water dynamics during sol-to-gel transition of poly (N-isopropylacrylamide) in concentrated aqueous solution. (27th January 2017) - Kametani, Shunsuke; Sekine, Sokei; Ohkubo, Takahiro; Hirano, Tomohiro; Ute, Koichi; Cheng, H.N.; Asakura, Tetsuo
Abstract: The focus of this work was on the significant changes in the water dynamics of aqueous poly (N-isopropylacrylamide) (PNIPAM) solution during sol-to-gel transition. Through the use of NMR (particularly two-dimensional 2 H NMR T1 -T2 relaxation) and rheology, we were able to show that below 34° C fast exchange occurs among free water and water molecules adsorbed on the surface of PNIPAM molecules. At 34° C, PNIPAM becomes aggregated; most of the water molecules are trapped in the PNIPAM aggregates, where water molecules with different dynamics are found. Above 34° C, PNIPAM molecules aggregate further to form a gel network; the free bulk water then becomes dominant at this stage. On the basis of these observations, a model where water molecules interact with PNIPAM in different ways during the transition was proposed. We believe that our experimental approach provides new information and fresh perspectives on the sol-to-gel transition of PNIPAM. Graphical abstract: Highlights: Change in water dynamics of PNIPAM solution during sol-to-gel transition is studied. Several states of water dynamics is revealed by 2D 2 H T1 -T2 NMR relaxation. An interaction model between water and PNIPAM during the phase transition is proposed.